Generalized bour s theorem - Güler, Erhan; Yaylı, Yusuf (Kuwait Journal of Science, 2015)
We give the classical isometric minimal helicoidal and rotational surfaces using generalized Bour’s theorem in Euclidean 3-space. Furthermore, we investigate the minimality and have same Gauss map of the surfaces.
Keywords: Gauss map; Gaussian curvature; Helicoidal surfaces; Mean curvature; Rotational surface